A cost-comparison of midwife-led compared with consultant-led maternity care in Ireland (the MidU study). Issue 11 (November 2015) - Kenny, Christopher; Devane, Declan; Normand, Charles; Clarke, Mike; Howard, Aoife; Begley, Cecily
Abstract: Objective: to compare the cost of maternity care between two midwife-led units, and their linked consultant-led units, following a large randomised trial in Ireland. Design: ethical approval was received for this unblinded, pragmatic randomised trial (MidU) funded by the Health Service Executive (Dublin North-East, Ireland), conducted 2004–2009. A comparison of costs analysis was conducted on the outcomes from the trial. Setting: two maternity units in Ireland, with 'alongside' midwife-led units. Participants: all women without risk factors for labour and birth who booked at the two maternity units before 24 weeks׳ gestation were assessed for inclusion. Consenting women ( n =1653) were centrally randomised on a 2:1 ratio (1101:552) to midwife-led or consultant-led care. Interventions: women randomised to consultant-led care received standard care. Women randomised to the midwife-led arm received midwife-led care provided by a small group of midwives in two units, situated ׳alongside׳ the consultant-led units, throughout pregnancy, birth and postnatal. Measurements: mean difference in clinician salaries, cost of care based on managers׳ data, known costs of postnatal bed days and costs of key interventions were measured. Findings: the average cost of caring for a woman allocated to the midwife-led units was €2598, compared to €2780 in the consultant-led units (average difference €182 per woman, analysed by 'intention to treat'). Key conclusions and implications for practice: care in these two midwife-led units costs less than care provided by the consultant-led units. Given the clinical findings, which showed that care provided in the midwife-led units is as safe as that in the consultant-led units and results in less intervention, more midwife-led units should be incorporated into maternity care in Ireland so that scarce resources can be used more effectively.